2008
DOI: 10.1002/pon.1353
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of a breast/ovarian cancer genetic testing decision aid used as a communication aid during genetic counseling

Abstract: Objectives: To evaluate the impact of a decision aid for women considering genetic testing for breast/ovarian cancer risk given during genetic counseling.Methods: One hundred and forty-eight women were randomized to receive the decision aid or a control pamphlet at the beginning of their first consultation with a genetic counselor. When the patient received the decision aid, it was used to complement consultation discussions about genetic testing. One hundred and ten (74.3%) women completed the first questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
89
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(89 citation statements)
references
References 36 publications
0
89
0
Order By: Relevance
“…Twenty-six of the 61 studies involved a patient decision aid [16,18,20,22,25,32,33,[47][48][49][50][51][52][53]56,[58][59][60][61]64,66,68,[72][73][74][75]. Four additional studies reported using education materials such as educational sessions or pamphlets but did not refer to them as decision aids [17,43,63,70].…”
Section: Summary Of Included Articlesmentioning
confidence: 98%
“…Twenty-six of the 61 studies involved a patient decision aid [16,18,20,22,25,32,33,[47][48][49][50][51][52][53]56,[58][59][60][61]64,66,68,[72][73][74][75]. Four additional studies reported using education materials such as educational sessions or pamphlets but did not refer to them as decision aids [17,43,63,70].…”
Section: Summary Of Included Articlesmentioning
confidence: 98%
“…Scale items are rated on a four point likert-type scale (0-4). This scale has demonstrated internal consistency reliability for GC patients [36][37][38]. Cronbach's alpha for the subscales were: depression subscale (a = .87) and anxiety subscale (a = .89).…”
Section: General Psychological Distressmentioning
confidence: 98%
“…This decision should be supported by a type of counseling that considers the condition of each individual in a specific moment of his/her personal life [7,8].…”
Section: Introductionmentioning
confidence: 99%